A Comprehensive Candidate Gene Study on Bronchial Asthma and Juvenile Idiopathic Arthritis. Issue 3 (9th June 2013) - Schubert, K.; von Bonnsdorf, H.; Burke, M.; Ahlert, I.; Braun, S.; Berner, R.; Deichmann, K. A.; Heinzmann, A.
Abstract : Bronchial asthma and juvenile idiopathic arthritis (JIA) are complex genetic diseases. As both represent chronic inflammatory diseases it is likely that they are at least partially influenced by the same genetic variants. One goal in dissecting the genetics of complex diseases is to identify a genetic risk profile. Therefore it is necessary to genotype polymorphisms in many different pathways. Thus we investigated 48 polymorphisms in 24 genes for association with asthma and/or JIA. Genotpying was performed on 231 asthmatic children, 86 children with JIA and 270 controls. Association analysis was performed by the Armitage's trend test. Furthermore haplotypes were calculated by FAMHAP. We found association of polymorphisms within IL-4, CTLA4 and TNFalpha with asthma and/or JIA. Furthermore, the polymorphisms showed an inverse distribution between children with asthma and JIA. However, we were not able to confirm association of most of the previously described candidate genes. We conclude from our data that it might be very difficult to identify genetic risk profiles for the development of asthma and/or JIA that would be valid across different populations. However, this study adds further evidence that the common genetic background of asthma and JIA is mainly based on polymorphisms in important TH1 and TH2 cytokines.